PENGARUH METODE JOLLY PHONICS BERBANTUAN MEDIA KARTU GAMBAR TERHADAP KETERAMPILAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Wanti Nur Istiqomah, - (2022)
This research is motivated by the low reading ability of students in the first grade of elementary school. The low ability of students to read at the beginning is also caused by the non-optimal face-to-face learning due to the urgency of the covid-19 virus. Then, the purpose of this study was to determine the effect of the jolly phonics method with the aid of picture card media on the students' early reading ability in grade 1 elementary school. This study uses a quantitative method, with a quasi-experimental research design in the form of a non-equivalent pretest-posttest control group design. The use of samples in this study amounted to 30 students in the experimental class and 30 students in the control class. The instruments used in this study are in the form of observations and tests. The test in this study was used in two stages, namely pre-test before the treatment was given and post-test after the treatment was given. Then, the results of this study indicate that the jolly phonic method has a significant and moderate effect on improving elementary school students' early reading skills. This can be seen descriptively from the average posttest score in the class that did not receive the jolly method treatment (control class) which was lower than the posttest score of the class that received the jolly method treatment (experimental class). In addition, it was concluded from the results of testing the average difference with the non-parametric method that there was a significant average difference between the experimental class and the control class so that the jolly method had an effect on elementary school students' early reading skills. Then the high influence is also found in the experimental class. With this, it is concluded that the jolly phonics method with the help of picture card media has an effect on the early reading ability of 1st grade elementary school students. Keyword : Jolly Phonic's Method, initial reading